2006
DOI: 10.1111/j.1467-2494.2006.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmentally realistic levels of ozone on stratum corneum function

Abstract: The impact of troposphere ozone (O(3)), the major oxidant in photochemical smog, on the overall wellbeing of skin is of considerable interest. To date, limited information is available on the impact of O(3) on human skin. Using a specially designed O(3) exposure chamber, we provide the first evidence that exposure of human skin to O(3) (0.8 ppm, 2-h time-weighted average) significantly reduced vitamin E by 70% and concomitantly increased lipid hydroperoxides by 2.3 fold in the superficial stratum corneum (SC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 44 publications
(53 reference statements)
3
51
0
Order By: Relevance
“…Ozonated olive oil is an amazing preparation because combines antibacterial activity with healing properties due to the slow release of oxygen in hypoxic tissues and the stimulation of fibroblasts proliferation. 212,213 Chronic ulcers and/or putrid wounds are one of the most distressing and difficult medical problems with which to deal and are caused by ischemia, diabetes, immunosuppression, and malnutrition. During the past decade the use of ozone derivatives in such cases has proved very beneficial, 143 but so far official medicine has not yet discovered this excellent preparation far more effective than ointments containing often ineffective antibiotics and corticosteroids, which delays healing.…”
Section: Chronic Infectious Diseasesmentioning
confidence: 99%
“…Ozonated olive oil is an amazing preparation because combines antibacterial activity with healing properties due to the slow release of oxygen in hypoxic tissues and the stimulation of fibroblasts proliferation. 212,213 Chronic ulcers and/or putrid wounds are one of the most distressing and difficult medical problems with which to deal and are caused by ischemia, diabetes, immunosuppression, and malnutrition. During the past decade the use of ozone derivatives in such cases has proved very beneficial, 143 but so far official medicine has not yet discovered this excellent preparation far more effective than ointments containing often ineffective antibiotics and corticosteroids, which delays healing.…”
Section: Chronic Infectious Diseasesmentioning
confidence: 99%
“…Ozone represents an important source of oxidative stress for skin; studies on animal models showed that ozone exposure leads to a progressive depletion of vitamin E and hydrophilic antioxidants (urate, ascorbate, glutathione) and to malondialdehyde (MDA) production in murine stratum corneum [20,21], inducing oxidative damage to lipids and leading to a perturbation of epidermal barrier function. A study performed on the skin of human volunteers showed that the ozone exposure significantly reduced vitamin E levels and increased lipid hydroperoxides in the stratum corneum, confirming that the effects of O 3 are limited to the superficial layers of the human skin [22]. In addition to increasing oxidative stress and decreasing of antioxidant skin defenses, ozone exposure is able to induce pro-inflammatory markers and increase the levels of heat shock proteins in mice skin [23].…”
Section: Introductionmentioning
confidence: 90%
“…He and his collaborators have reported that simultaneous exposure of human arms to either oxygen or ozone does induce only a moderate state of oxidative stress without signs of either skin dryness or erythema as it occurred by the occasional exposure of human skin to gaseous ozone (0.8 ppm, 2-h time-weighted average) [46]. It was also shown that ozone was unable to penetrate the stratum corneum and to catalyse the Criegee reaction in spite of a low water availability.…”
Section: Topical Applications Of Gaseous Ozonementioning
confidence: 97%